How video attributes influence farmer learning about maize postharvest handling practices and technologies in kakumiro district, Uganda (International Journal of Agricultural Research, Innovation and Technology, 2019)
In Sub-Saharan Africa, video has been earmarked as an important tool to enhance learning among smallholder farmers. The study evaluated how the inherent video attributes influence learning about postharvest handling practices and technologies from the perspective of maize farmers in Kakumiro district of Uganda; using the case of Access Agriculture maize videos. An action-oriented research involving showing of four videos, on-site participant observation, six key informant and 50 exit individual interviews were conducted in February 2019. While thematic-content analysis was applied for qualitative data, quantitative data were analyzed using SPSS 18.0 version. Our results clearly illustrate that the video’s ability to influence farmer learning depends on the complementarity of its positive attributes including: demonstration ability, attractiveness and clarity of images, ability to arouse interest and curiosity; thus, fostering interactions among viewers. The nature of video content in terms of clarity, practicability, relevance, applicability and content sequencing are also perceived to be key attributes of video in enhancing learning among the viewers. However, the effectiveness of video is likely to be compromised by the socio-economic and cultural factors more especially if such factors are not well taken care of during the filming process. If possible, when developing videos for farmer learning, focus should be on creating local content that is context specific, which farmers can enjoy and relate to for easy adaptation and eventual application.Int. J. Agril. Res. Innov. & Tech. 9 (1): 58-65, June, 2019